Limit analysis of locally reinforced masonry arches. (15th November 2022) - Nela, Bledian; Jiménez Rios, Alejandro; Pingaro, Marco; Reccia, Emanuele; Trovalusci, Patrizia
Abstract: The use of composite on the strengthening and retrofitting of masonry structures over the past few decades has gained considerable importance. In this paper, the influence of partial reinforcement on the structural response of masonry arches is studied. An upper bound limit analysis numerical approach has been implemented to compute the collapse multipliers and reproduce the collapse mechanisms of two different study cases by increasing the cohesion value of the reinforced inter-block joints. The results thus obtained, have been compared to numerical simulation outcomes reported by other authors on the literature. The numerical approach adopted on this work, which requires few input parameters, is relatively fast in comparison to alternative numerical simulation methods, provided good agreement in terms of collapse loads and mechanisms. Highlights: Collapse behaviour of masonry arches subject to horizontal live loads. Local reinforcement of masonry arches with different shapes. Impact of the infill consideration for the reinforced and unreinforced scenarios.